Systematic Literature Review on Digital Marketing in Women’s Healthcare Using the PRISMA Model - Huda, Nasrin; Suanda, Julinawati; Ahamed, Nor’izah (Bangladesh Journal of Medical Science, 2025)
Digital marketing is a rapidly emerging topic in both academic and industry sectors, particularly in the field of marketing. While numerous studies have explored the relationship between digital marketing and health, the exact scope and focus of this research remain unclear. This study conducted a systematic literature review (SLR) using R software to identify the number of papers addressing digital marketing and health. The review revealed a significant research gap: although there is substantial research on consumer behavior, customer loyalty, the impact of digital marketing during COVID-19, and product purchase decisions, few studies have examined the role of digital marketing in health campaigns. More specifically, there is a notable lack of research on digital marketing’s role in women’s healthcare campaigns. This study aims to fill this gap by investigating the role of digital marketing in women’s healthcare campaigns within private hospitals in Bangladesh. By analyzing 785 relevant articles, the review found that digital marketing strategies, such as social media campaigns, mHealth apps, and telehealth services, are effective in increasing health awareness, engagement, and outcomes among women. The findings highlight the global interest and application of digital marketing in healthcare, demonstrating its potential to bridge geographic and socio-economic barriers to healthcare access. The study concludes with practical recommendations for healthcare providers and policymakers to leverage digital marketing effectively. This research contributes to the literature by providing insights into how digital marketing can enhance women’s healthcare, particularly in regions with limited access to traditional healthcare services, and suggests directions for future research to explore this emerging field further. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 373-384